Octreotide and lanreotide decrease ovarian ischemia–reperfusion injury in rats by improving oxidative and nitrosative stress. Issue 10 (3rd August 2020) - Kalyoncu, Senol; Yilmaz, Bulent; Demir, Mustafa; Tuncer, Meltem; Bozdag, Zehra; Ince, Onur; Akif Bozdayi, Mehmet; Ulusal, Hasan; Taysi, Seyithan
Abstract: Aim: To investigate the protective effect of octreotide and lanreotide on ovarian damage in experimental ovarian ischemia–reperfusion injury. Methods: Fifty‐six rats were separated into seven groups; group 1: sham group, group 2: surgical control group with 3‐h torsion and detorsion, group 3: 0.02 mg/kg s.c. octreotide 30 min before 3‐h torsion, group 4; octreotide just after detorsion for 7 days, group 5: octreotide 30 min before torsion and just after detorsion for 7 days, group 6: single time 20 mg/kg s.c. lanreotide before torsion, group 7: single time lanreotide just after detorsion. Results: All histopathological scores except congestion were significantly lower in group 1 than other groups. In addition, hemorrhage (group 2 vs 4: P  < 0.05), degeneration (group 2 vs 4: P  < 0.05, group 2 vs 5: P  < 0.01 and group 2 vs 6: P  < 0.05) and total damage score (group 2 vs 4: P  < 0.05, group 2 vs 5: P  < 0.05, group 2 vs 6: P  < 0.05 and group 2 vs 7: P  < 0.05) were significantly lower than other groups. Moreover, ovarian tissue total oxidant status and oxidative stress index levels were significantly decreased in groups 5 (both P  < 0.05) and 7 (both P  < 0.05) when compared to group 2. Furthermore, tissue levels of peroxynitrite were significantly higher in group 2 than groups 1, 3 and 5 (all P  < 0.05). Conclusions: Octreotide and lanreotide have a protective role against ischemia–reperfusion damage in rat torsion detorsion model by improving histopathological and biochemical findings including tissue levels of total oxidant status, oxidative stress index and peroxynitrite.